Adopting online lecturing for improved learning: A case study from teacher education - Quinn, Marie; Kennedy-Clark, Shannon (Journal of University Teaching and Learning Practice, 2015)
This paper presents the results of a study that examined the integration of video lectures into a pre-service teacher unit of study. The aim of the research was to ascertain how students used the pre-recorded videos to complement their learning. The focus was on the pedagogy, and explored three factors: convenience, self-regulation of learning and design to aid learning. A mixed method approach to the data collection was used. Data sources included reflective journals, surveys and semi-structured interviews. An analysis of the data indicates that the pre-service teachers viewed the use of pre-recorded lectures positively and that they were a useful resource for self-study. The use of a webcam was also viewed positively as a design feature of the lectures. Overall, the responses to the innovation were positive.